Indirect transfer of resistance to imipenem in a strain of Pseudomonas aeruginosa - Krcméry, V; Lesicka, M; Blahova, J; Schäfer, V (Journal of chemotherapy (Florence, Italy), 1991)
Determinants of resistance of imipenem can be, in Pseudomonas aeruginosa strains resistant to this drug, transferred by transduction with wild-type phages as well as mobilized for conjugal transfer, as demonstrated by the indirect selection procedure. Exconjugants obtained in the latter type of experiments do not transfer imipenem resistance determinant to further recipient strains(s) by conjugation. Mobilized imipenem resistance is of non-hydrolytic character and its biochemical mechanism is unknown at present.
Keywords: imipenem; antibiotická rezistence; Imipenem; Cefazolin; Phenotype; cefotaxim; konjugace genetická; Pseudomonas aeruginosa; Cefotaxime; Drug Resistance, Microbial; fenotyp; Conjugation, Genetic; cefazolin